Heatwave-driven persistent microbes threaten the resilience of Mediterranean coral holobionts - Camille Prioux; Christine Ferrier-Pagès; Thibaut Lamarca; Denis Allemand; Romie Tignat-Perrier (Environmental Microbiome)
Abstract Background The climate crisis poses a serious threat to octocorals in the Mediterranean Sea as marine heatwaves (MHWs) not only impair coral metabolism but also disrupt the complex symbiosis between the coral host and its microbiome. Since octocorals are the foundation species of the Mediterranean animal forests, understanding their resilience, i.e. ability to recover and survive to MHWs, is crucial to predict their viability under future climatic conditions. Using amplification of 16 S and 18 S rRNA genes for metabarcoding and qPCR analyses to follow the changes in bacterial microbiome and eukaryome as well as host response under stress and recovery conditions, this study provides the first comprehensive assessment of the resilience of an iconic Mediterranean octocoral (the red coral Corallium rubrum) to a mild (19 °C) and more severe (23 °C) heat stress. Results The results of this work indicate a stress response of the host to elevated temperatures, even under mild temperature. The eukaryome was highly sensitive to heat stress and underwent rapid structural changes among the dominant microeukaryotes. In contrast, the relative and absolute abundance of the major bacterial symbionts remained stable throughout the stress. However, heat stress led to a significant increase in the abundance of some taxa such as Vibrionaceae that persisted after a week of recovery. Conclusions While the host recovered from the stress, and the microbiome largely returned to its original composition during recovery, the results highlight the persistent presence of some taxa that might compromise the short-term resilience of octocoral holobionts. This study provides new information on how octocoral holobionts respond to MHWs in the Mediterranean Sea. This knowledge is crucial for the development of effective, science-based strategies for coral protection and restauration.